Legal Aspects of Personal Data Protection and the Issues of Competition in Digital Marketplaces - A. Kolawole (Journal of Digital Technologies and Law, 2024)
Objective: to develop approaches and proposals to improve the legal mechanisms for the personal data protection in the context of the evolving digital markets and the growing digital competition.Methods: the article is prepared based on formal legal and comparative legal research methods.Results: the unique features of digital markets are shown, which must be taken into account to achieve the goals of antimonopoly legislation. It is marked that the fundamental elements of the digital market include the big data concept and big data analytics, which, based on digital platforms, are capable of producing many direct and indirect network effects. The latter require understanding for an effective antitrust response and the application of appropriate legislation. The author proves that the growth of digital platforms as a business model and vital infrastructure of the digital economy should be viewed as a factor in improving legal regulation of relations in the sphere of data protection and confidentiality. The paper identifies the potential of digital platforms for assessing the current market power and the impact of competition on limiting this power. The data are considered as an integral component of the overall competitive market landscape. The current European Union regulation in the field of digital platforms and personal data protection is analyzed. The author identifies difficulties associated with the creation and application of effective regulations governing the activities of digital platforms. The article proves that antimonopoly authorities need to change approaches to analytics in order to take into account the distinctive features of digital platforms. It is noted that such changes may require legislative reforms and revision of procedures to match the rapid development of these markets and ensure that any potentially anticompetitive behavior is thoroughly investigated.Scientific novelty: the research contributes to the development of approaches to determining indicators of ensuring the personal data confidentiality under the digitalization of markets and to evaluating the effectiveness of antimonopoly legislation and its application in a new competitive environment.Practical significance: the results obtained can be used as a basis for improving antimonopoly and personal data protection legislation, as well as legal regulation of digital platforms in general.